O vivo no telejornalismo: uma tipologia de finalidades, funções e formatos - Backes, Vanessa Cristina (2024)
Among the possible configurations of news on television, this research is interested in the format recognized as "vivo" (live reporting) by Brazilian journalism, consisting of the reporter's participation, enunciating information, with image and sound capture simultaneously with the transmission, at the very location of an event. From a technological point of view, live reporting in television journalism is conditioned by the development of equipment capable of capturing, transmitting and receiving audiovisual content. From a journalistic point of view, this format of news has always been at the service of covering ongoing events at the time the newscasts were broadcast. However, in the current media ecosystem, characterized by mobility and ubiquity, and strongly influenced by the language of the Internet, live shot has increasingly gained space in television news programs, being, in many of them, the predominant and preferred format. Thus, this research has as its backdrop the nature of television journalism in reformulating its language according to the development of new technologies. And, in this digital and convergent context, it investigates the hypothesis of live reporting serving a set of other interests, crossed by the influence of the contemporary media environment, adding new characteristics to those inherent to this news model. From this perspective, the research's general objective is to analyze the conformation of television news called live reporting, with a view to identifying its purposes, functions and formats, relating them to the predominant values in the contemporary media environment. To achieve this, the methodology was designed based on the combination of two levels of analysis: contextual, through the lens of Media Ecology, by researchers such as McLuhan (2007), Scolari (2008, 2015), Canavilhas (2015), Seib (2001) and Strate, Braga and Levison (2019) and others; and the textual, through the perspective of Discursive Semiotics, from researchers such as Greimas and Courtés (2016), Duarte (2022, 2012, 2007, 2006), Castro (2012), Jost (2007, 2004) and others. The corpus of analysis was composed of live shots broadcast on five regional morning news programs on Rede Globo de Televisão, considering them paradigmatic with regard to live language. Among the results obtained by the research is the development of a live typology, with 11 possible types of live broadcasts identified in these television news programs, considering their purposes, functions and formats, namely: call live call, news live, synchronous live, report live, interview live, testimony live, bulletin live, portrait live, mosaic live, self-referential live and selfie live. The research demonstrates that live is at the service of other purposes, functions and formats beyond the coverage of ongoing events, and can be used by television news programs in self-promotion strategies, interaction with the viewer, attracting an audience, or even to simplify the editing process, expand its production capacity for audiovisual content, among others. Valuing live reporting also requires specific skills from journalists to develop this format along the lines in which it has been applied in regional morning news programs, such as rhetorical and improvisational skills.